2021
DOI: 10.1007/s13595-021-01107-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular control to salt tolerance mechanisms of woody plants: recent achievements and perspectives

Abstract: Key message Woody plants have salt-tolerant mechanisms similar to those developed by non-woody plants. Among others, compartmentalization of ions, production of compatible solutes, synthesis of specific proteins and metabolites, and induction of transcriptional factors are the most relevant. Woody plant-associated microbial interactions as well as naturally stress-adapted trees are resources that deserve to be deepened to fully understand the tolerance mechanisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 183 publications
(146 reference statements)
0
9
0
Order By: Relevance
“…The ability to store water and solutes in their tissues guarantees the growth and development of these plants under salt stress conditions. Salinity tolerant plants can selectively accumulate ions and thus maintain the osmotic adjustment, ensuring water absorption (Llanes et al, 2021). When evaluating the salinity tolerance of cactus, Schuch and Kelly (2008) observed that saguaro cactus and golden barrel cactus were tolerant to all salinity levels without altering the total dry mass content; these cactus species relied on osmotic adjustment based on increased osmotic potential and higher concentrations of sodium and chloride in the stem tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to store water and solutes in their tissues guarantees the growth and development of these plants under salt stress conditions. Salinity tolerant plants can selectively accumulate ions and thus maintain the osmotic adjustment, ensuring water absorption (Llanes et al, 2021). When evaluating the salinity tolerance of cactus, Schuch and Kelly (2008) observed that saguaro cactus and golden barrel cactus were tolerant to all salinity levels without altering the total dry mass content; these cactus species relied on osmotic adjustment based on increased osmotic potential and higher concentrations of sodium and chloride in the stem tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Woody plants with longer life cycles and larger body sizes are more tolerant to harsh conditions such as habitat fragmentation or climate change ( Harper, 1977 ; Petit and Hampe, 2006 ; Sork et al., 2013 ; Olson et al., 2016 ; Llanes et al., 2021 ). Because shrubs have a shorter life cycle and can settle in new suitable areas more quickly than trees, the overall suitable area for shrubs (+8.52%) increased more, and the highly suitable area for shrubs (–0.22%) decreased less than that of trees (–42.81%) under future climate change projections ( Hiernaux et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, an in vitro approach was used to highlight whether cultured excised roots could detect similar responses in proteomics profiles compared to using roots from plants grown by traditional methods. Even though there are no proteomics studies on the responses of woody plants to salt stress, according to [19][20][21], woody plants have salttolerant mechanisms similar to those developed by non-woody plants. Several differential proteomics studies on the responses of herbaceous plant roots to salt stress have been published in recent decades [18,[22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%